Use of phonolite associated with vinasse in sugarcane cultivation (Research, Society and Development, 2022)
The sugarcane crop is quite demanding in terms of fertilization, as in the case of potassium (K), this is applied to the crop through vinasse, a by-product of the alcohol and sugar industry, which is generated in large quantities by the mills, or by fertilizers such as potassium chloride, an alternative to these products is the use of rock dust, which have significant K2O contents in their composition, as in the case of phonolite. Therefore, the objective of the experiment was to evaluate the effect of phonolite and the association between phonolite and vinasse in sugarcane cultivation, as well as the effect of these products on technological attributes. The experiment was conducted in the field in January 2018, in an Oxisol, clayey texture, located in the Agricultural Sciences Sector, on the campus of Universidade José do Rosário Vellano – Unifenas, Alfenas, MG. The experiment was installed in a randomized block design, with five treatments and three replications, consisting of 15 experimental units. The 5 treatments are constituted by: without application (control); potassium chloride; vinasse; phonolite; phonolite + vinasse. The following parameters were evaluated: number of tillers, ton of cane per hectare, soluble solids, total sugars recovered and apparent sucrose in sugarcane. The application of phonolite and the association between phonolite and vinasse did not change the attributes evaluated in the cultivation of sugarcane under these conditions of study.